Nurse-led counselling programme on the adherence to eye patch application among children with amblyopia: a randomised control trial - Srishti Raj; Savleen Kaur; Mona Duggal; Shivani; Sushma Kumari Saini (BMJ Open Ophthalmology)
Objective To assess the impact of the nurse-led counselling programme on eye patch application for improvement of adherence to eye patch application and vision among children with amblyopia.Material and methods A randomised control trial was done at the paediatric clinic in the eye outpatient department of a tertiary care institute in North India. A total of 70 children with amblyopia were enrolled in the study by using total enumeration sampling techniques and randomised into experimental and control groups with 35 children in each group. Data were collected by interviewing the children with amblyopia and their parents as per the interview schedule. A protocol for nurse-led counselling on the adherence to eye patch application was developed. The intervention included counselling sessions, demonstrations and booklets for the experimental group. A performa for maintaining daily records of the time and duration of eye patch application was given to parents of the experimental group. Eight telephonic follow-ups were done with the experimental group of patients to motivate parents to adhere. Standard care was given to the children of the control group. Both groups were finally evaluated at third month on adherence to eye patch application and visual acuity.Result The adherence to eye patch application, vision (as per logMAR chart) knowledge and practices of eye patch application was significantly better in the experimental group as compared with the control group (p<0.01).Conclusion The nurse-led counselling programme demonstrated improvement in visual outcomes and adherence to eye patch application.